Trans‐Amazonian natal homing in giant catfish. Issue 5 (18th April 2016) - Duponchelle, Fabrice; Pouilly, Marc; Pécheyran, Christophe; Hauser, Marilia; Renno, Jean‐François; Panfili, Jacques; Darnaude, Audrey M.; García‐Vasquez, Aurea; Carvajal‐Vallejos, Fernando; García‐Dávila, Carmen; Doria, Carolina; Bérail, Sylvain; et al.
Summary: Knowledge of fish migration is a prerequisite to sustainable fisheries management and preservation, especially in large international river basins. In particular, understanding whether a migratory lifestyle is compulsory or facultative, and whether adults home to their natal geographic area is paramount to fully appraise disruptions of longitudinal connectivity resulting from damming. In the Amazon, the large migratory catfishes of the Brachyplatystoma genus are apex predators of considerable interest for fisheries. They are believed to use the entire length of the basin to perform their life cycle, with hypothesized homing behaviours. Here, we tested these hypotheses, using the emblematic B. rousseauxii as a model species. We sampled adults close to major breeding areas in the Amazon basin (upper Madeira and upper Amazonas) and assessed their lifetime movements by measuring variations in 87 Sr/ 86 Sr along transverse sections of their otoliths (ear stones) using laser ablation multicollector mass spectrometry (LA‐MC‐ICPMS). We demonstrate that larvae migrate downstream from the Andean piedmont to the lower Amazon, where they grow over a protracted period before migrating upstream as adults. Contrary to prevailing inferences, not all fish spend their nursery stages in the Amazon estuary. By contrast, the passage in the lower or central Amazon seems an obligate part of the life cycle. We further evidence that most adults home to their natal geographic area within the Madeira sub‐basin. Such long‐distance natal homing is exceptional in purely freshwater fishes. Synthesis and applications . By using otolith microchemistry, we were able to demonstrate a seemingly compulsory basin‐wide migratory life cycle of large Amazonian catfishes. This makes them the organisms performing the longest migrations (>8000 km) in fresh waters. This exceptional life history is already jeopardized by two dams recently built in the Madeira River, which block a major migration route and access to a substantial part of their spawning grounds. Major impacts can be anticipated from the current and forthcoming hydroelectric development in the Amazon basin, not only on the populations and fisheries of this apex predator, but also on Amazonian food webs through trophic cascades. Abstract : By using otolith microchemistry, we were able to demonstrate a seemingly compulsory basin‐wide migratory life cycle of large Amazonian catfishes. This makes them the organisms performing the longest migrations (>8000 km) in fresh waters. This exceptional life history is already jeopardized by two dams recently built in the Madeira River, which block a major migration route and access to a substantial part of their spawning grounds. Major impacts can be anticipated from the current and forthcoming hydroelectric development in the Amazon basin, not only on the populations and fisheries of this apex predator, but also on Amazonian food webs through trophic cascades.